Sex-Specific Analysis in Patients Undergoing Talar OsteoPeriostic Grafting from the Iliac Crest (TOPIC) for Large Osteochondral Lesions of the Talus - Jari Dahmen MD; Arianna Gianakos DO; Julian Hollander Bsc; Quinten Rikken MD; Sjoerd Stufkens MD, PhD; Gino M M.M.J. Kerkhoffs MD, PhD (Foot & Ankle Orthopaedics)
Category: Sports; Ankle Introduction/Purpose: Talar OsteoPeriostic grafting from the Iliac Crest (TOPIC) is a novel technique for the treatment of large osteochondral lesions of the talus. It is the purpose of the present study to assess the gender-specific differences in the presentation and outcomes following TOPIC between male and female patients. Methods: A prospective comparative analysis was performed comparing consecutive female and male patients having been treated by the press-fit TOPIC procedure. Clinical comparative assessment pre-operatively and at 12 months of follow-up included determination of the Numeric Rating Scale (NRS) scores for pain during walking (primary outcome), at rest, and during stair-climbing. The Foot and Ankle Outcome Score (FAOS) was also assessed. A computed tomography (CT) scan was performed for lesion size, morphology and localization determination pre-operatively as well as 10-12 weeks postoperatively to assess union of the distal tibial osteotomy site and at 1 years postoperatively to assess consolidation of the graft as well as cyst development in the graft. Results: A total of 48 patients (30 women, 18 men) were eligible for inclusion. Both men and women demonstrated significant functional improvements post-operatively concerning the clinical outcomes with no significant differences between men and women (n.s.) except for a significantly greater improvement in postoperative FAOS pain scores in women. Men presented with OLTs significantly larger in both surface area (208 mm 2 for males versus 155 mm 2 for females, p< 0,05) as well as lesion volume (3.0 cm 3 for males versus 1.8 cm 3 for females, p< 0.05). At 1-year post-operatively, all patients with a CT scan (n=47) showed graft consolidation. Cyst formation was present in 11 females (37% of the group) and 10 males (59% of the group), respectively (p=0.24). There were no statistical differences in complication rates following the TOPIC procedure. Conclusion: Both male and female patients showed clinically relevant improvements in the clinical outcomes after undergoing the TOPIC procedure, with significant differences in pre-operative size. There were no statistical differences in complication rates following the TOPIC procedure, although a higher proportion of women did require hardware removal. TOPIC procedure is a good treatment strategy for large OLTs in both men and women.